THE REALIZATION OF THE PROGRAMME CONTENTS FOR PHYSICAL EDUCATION IN THE SECOND GRADE OF PRIMARY SCHOOL BASED ON MINIMAL REQUIREMENTS - Nevenka Zrnzević (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
tested students (74 male and 79 female students) of the second grade of primary schools in Trstenik. The four variables were applied (shooting the ball at horizontal target from the distance of 10 m; waging the ball on the spot by left and right hand; low beam: walking with appealing, squating, uprighting, three connected spining ahead) by which the efficiency of programme contents realization has been evaluated. The results were statistically evaluated and tabulated. The results of analysis have showed that male and female students are not statistically distinguished (p = 0,181) in applied variables for evaluation of motoric information adoption. According to the results male students are more homogenic than female students